Iklan Layanan Masyarakat Tentang Pelecehan Seksual Menggunakan Teknik Sinematografi - Tri Nur Nugraha Satria; Noor Alam Hadiwijaya; Yusni Nyura (JURNAL VOKASI TEKNIK, 2025)
Public Service Announcements (PSAs) are an effective medium for conveying social messages to the public. This study discusses sexual harassment in the form of catcalling by using cinematographic techniques, particularly Types of Shots, to deliver messages clearly and engagingly. The method used is the Multimedia Development Life Cycle (MDLC), which includes the stages of Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The result of the study is a PSA video lasting 2 minutes and 43 seconds, uploaded to YouTube, incorporating various Types of Shots such as Long Shot, Medium Shot, Close-Up, and others to enhance the effectiveness of message delivery.